STATISTICAL PROCEDURES IN THE QUALITY CONTROL OF THE GEARS - K. WECZEROWSKI; JA. UNIEJEWSKI (Advanced Engineering Research, 2006)
The production technology of the quality control, it’s strategy and planning in the process planning with the ability of aid with the computer is the important component of the improvement of the quality  stability of the production according to the set of standardsPN-EN29000. The review and the essence of works, which are carrying out in this field in the Division of Process Planning and Technological Design Systems were described.